2022
DOI: 10.1002/jha2.404
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of immunologic autograft engineering

Abstract: Our phase III trial reported that autograft‐absolute lymphocyte count (A‐ALC) improved survival post‐autologous peripheral blood hematopoietic stem cell transplantation (APBHSCT) for a short‐term follow‐up of 2 years. We evaluated retrospectively in our phase III trial patients that the A‐ALC still confers survival benefit with a longer follow‐up. With a median follow‐up of 127.6 months, patients infused with an A‐ALC ≥ 0.5 × 109 cells/kg experienced better overall survival (HR = 0.392, 95% confidence of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Giving a higher number of lymphocytes after high‐dose chemotherapy might improve survival. In fact, a randomized study suggests that higher infused lymphocyte counts after high‐dose therapy are associated with better long‐term outcome in NHL patients 63,64 . In several retrospective analyses of NHL patients, early immune recovery (absolute lymphocyte count on d + 15 > 0.5 × 10 9 /L) after AHCT has been associated with better outcome especially in NHL patients 65 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giving a higher number of lymphocytes after high‐dose chemotherapy might improve survival. In fact, a randomized study suggests that higher infused lymphocyte counts after high‐dose therapy are associated with better long‐term outcome in NHL patients 63,64 . In several retrospective analyses of NHL patients, early immune recovery (absolute lymphocyte count on d + 15 > 0.5 × 10 9 /L) after AHCT has been associated with better outcome especially in NHL patients 65 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, a randomized study suggests that higher infused lymphocyte counts after high-dose therapy are associated with better longterm outcome in NHL patients. 63,64 In several retrospective analyses of NHL patients, early immune recovery (absolute lymphocyte count on d + 15 > 0.5 Â 10 9 /L) after AHCT has been associated with better outcome especially in NHL patients. 65 In general, hematologic recovery post-AHCT has been comparable with patients mobilized without PLER, but we have observed somewhat slower platelet recovery in patients receiving preemptive PLER for poor mobilization at least in NHL patients.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up at median 10.6 years was conducted with all of the patients who were recruited and completed the phase III trial: the 13-years OS rate was 54% for the A-ALC ≥ 0.5 × 10 9 cells/kg group and 28% for the A-ALC < 0.5 × 10 9 cells/kg group ( p < 0.0007). The 13-years PFS rate following A-ALC ≥ 0.5 × 10 9 cells/kg was 46% versus 17% for those with an A-ALC < 0.5 × 10 9 cells/kg [ 22 ]. However, patients still relapsed despite being infused with an A-ALC ≥ 0.5 × 10 9 cells/kg.…”
Section: Infusion Of Autograft-absolute Lymphocyte Countmentioning
confidence: 99%
“…However, looking at the Kaplan–Meier survival curves, the differences in survival between the group that had lower autograft NK cells compared with the group that had higher number of autograft NK cells showed that the 5-year OS rates were approximately 80% for the patients who received autograft NK cells < 0.5 × 10 6 cells/kg, versus 70% for the patients infused with autograft NK cells ≥ 0.5 × 10 6 cells/kg ( p = 0.092), and the median follow-up for both groups has not been reached. The 5-year PFS rates were approximately 75% for the patients received autograft NK cells < 0.5 × 10 6 cells/kg versus 55% for the patients infused with autograft NK cells ≥ 0.5 × 10 6 cells/kg ( p = 0.048), and the median follow-up for both groups have not been reached [ 37 ]. In contrast, the same group reported superior overall survival in non-high risk cytogenetics multiple myeloma patients that received autograft NK cells ≥ 2.5 × 10 6 cells/kg (the 5-year OS rates approximately 95%) compared with patients that received autograft NK cells < 2.5 × 10 6 cells/kg (the 5-year OS rates approximately 65%) ( p < 0.006) [ 38 ].…”
Section: Infusion Of Autograft-natural Killer Cells and Survivalmentioning
confidence: 99%
“…CXCL12/CXC4 is a chemokine signal for NK cell trafficking. Multiple studies have shown that the combination of Plerixafor plus G-CSF mobilized more NK cells compared with just G-CSF for mobilization [ 37 , 65 , 66 , 67 , 68 ].…”
Section: Engineering An Autograft Natural Killer Cell and Enhancing N...mentioning
confidence: 99%